The Asset Portfolios of Native-born and Foreign-born Households - Hildebrand, V.A.; Cobb-Clark, D (My University, 2009)
This paper analyses the net worth and asset portfolios of native- and foreign-born Australian families. Specifically, we estimate a system of asset equations with an adding-up constraint imposed to control for diversity in household wealth. We find that the wealth of mixed and native-born couples is not significantly different; however, immigrant-only couples have approximately $162 000 less wealth than native-born couples. Relative to equally wealthy native-born couples, immigrant-only couples hold substantially more wealth in their homes and less in the form of vehicles. Mixed couples and single individuals allocate their wealth across assets in the same way their native-born counterparts.
Economic Record
Keywords: Finance; Finance -- Assets; Culture -- Immigrants; Culture; Income, wealth and finances; Migration and settlement; Culture; Finance; Immigrants; Assets; Migration and settlement; Income, wealth and finance